Pengaruh Terapi Bekam Terhadap Tekanan Darah Pasien Hipertensi Esensial di Rumah Bekam Denpasar Mei-Juni Tahun 2014 - Bahar Sangkur G Sangkur G; Dini Nurmuharomah; Inge Nandya; Ni Putu Diah; Nurtyana Utami; I Nyoman Sutarsa (Universitas Udayana, 2017)
Cupping is a therapy that aims to rid the body of blood containing toxins by slicing thin or small punctures on the skin surface. So far growing public confidence especially Muslims that cupping could be hypertension therapy based on reason that cupping was the recommended therapeutic from Prophet Muhammad can cope with various diseases. However, nowadays, there is not may evidence based data that support this matter. Regarding of this matter, the study was conducted with the aim to illustrate the impact of cupping therapy on reduction of blood pressure in patients with essential hypertension who underwent cupping at Rumah Bekam Denpasar by using quantitative descriptive approach. This research involving 27 samples from May until June 2014. The blood pressure measurements were taken before and after cupping using two different types of sphygmomanometer to minimize bias. The result showed that there is a decrease in blood pressure in hypertensive patients undergoing cupping, where the use of digital sphygmomanometer blood pressure decrease of 8.54 mmHg for systole and 5.53 mmHg for diastole. While the use of mercury sphygmomanometer, a decrease in blood pressure were obtained at 7.44 mmHg for systole and 4.59 mmHg for diastole. Conclusion on this study showed that cupping can decrease the blood pressure on patients with hypertension. Keyword : Cupping, hypertension, blood pressure reduction